2007
DOI: 10.1159/000112027
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcome and Its Prediction in First-Episode Schizophrenia – A Naturalistic Study

Abstract: Background: The literature suggests that the early course of schizophrenia is a strong predictor of long-term outcome. We sought to test this notion in a sample of first-episode patients. Sampling and Methods: Forty patients with a first episode of DSM-IV diagnoses of schizophrenia, schizoaffective, or schizophreniform disorder were assessed with well-established instruments such as the Positive and Negative Syndrome Scale and the Strauss-Carpenter Scale. Reassessment was performed 14 months later and included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 107 publications
1
13
0
Order By: Relevance
“…These results go along with previous research in adults suggesting that the adherence to medications is one of the main factors associated with short-term outcome [40,41]. Recent observations suggest that outcome in early-onset psychosis in specific therapeutic settings may be better that in adult-onset psychoses [7]; the role of proper therapeutic intervention in this group of patients seems to be crucial.…”
Section: Discussionsupporting
confidence: 83%
“…These results go along with previous research in adults suggesting that the adherence to medications is one of the main factors associated with short-term outcome [40,41]. Recent observations suggest that outcome in early-onset psychosis in specific therapeutic settings may be better that in adult-onset psychoses [7]; the role of proper therapeutic intervention in this group of patients seems to be crucial.…”
Section: Discussionsupporting
confidence: 83%
“…Males also improved less, so after 1 year there were more males in the unremitted group (7/12, 56%) and more females in the remitted group (16/27, 60%). All this shows interaction between gender and remission, consistent with gender as a potent determinant of outcome [1,4,29,30]. Accordingly, we stratified our analysis by gender, using a median split of GAF at 1 year for males and females to minimize data skewness.…”
Section: Resultsmentioning
confidence: 77%
“…We know that factors generally conducive to a good response include being female [1], a shorter illness period [2], fewer negative symptoms and lower global psychopathology scores [3], accepting treatment [1,4], early response, lack of hospitalisation, preserved functioning, being married and having social support [5]. Historically, the course and outcome of schizophrenia was believed to be Kraepelinian, but this notion has been challenged by current nosological debate and awareness that ‘prognosis is better than traditionally assumed' [6].…”
Section: Introductionmentioning
confidence: 99%
“…Another reason could be related to the heterogeneity of schizophrenia. A 1-year naturalistic study exploring the outcome of first-episode schizophrenia reported that subgroups of patients experienced a significant decrease in symptom levels, rated by the PANSS, whereas the symptoms increased in another subgroup [19] .…”
Section: Discussionmentioning
confidence: 99%